1985
DOI: 10.1159/000242105
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Production by the Human Fetus at Term Gestation

Abstract: In a previous study, we demonstrated the complete dependence of the human fetus on the mother for its glucose needs. As alanine is considered the major glucogenic amino acid synthesized endogenously and an important source of urea nitrogen, in the present study we examined whether the human fetus at term gestation can produce alanine. 5 normal pregnant women, undergoing elective cesarean section, were given a constant infusion of [2,3-13C2]alanine in trace quantities for a period of 4 h p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…There may be, however, quantitative differences in the degree of limitation. Gilfillan et al (1) reported that the umbilical venous and arterial plasma enrichments of 13 C-labeled tracer alanine infused at a constant rate into the maternal circulation were ϳ44 and 25%, respectively, of maternal peripheral venous enrichment in term human pregnancies studied at the time of cesarean section. These ratios are greater than the one observed in the present study for the maternally infused [ 13 C]alanine (ϳ6 and 4%) and suggest a larger contribution of the maternal alanine flux across the human placenta to fetal alanine turnover.…”
Section: Discussionmentioning
confidence: 99%
“…There may be, however, quantitative differences in the degree of limitation. Gilfillan et al (1) reported that the umbilical venous and arterial plasma enrichments of 13 C-labeled tracer alanine infused at a constant rate into the maternal circulation were ϳ44 and 25%, respectively, of maternal peripheral venous enrichment in term human pregnancies studied at the time of cesarean section. These ratios are greater than the one observed in the present study for the maternally infused [ 13 C]alanine (ϳ6 and 4%) and suggest a larger contribution of the maternal alanine flux across the human placenta to fetal alanine turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma insulin was measured by a double antibody radioimmunoas say. All the analytical methods have been reported previously from this laboratory [7][8][9], All data are reported as mean ± SD. Statistical analysis was per formed either by descriptive (mean, standard deviation, 95% confi dence intervals (Cl) or by least square linear regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration gradients and transport of various sub strates and nutrients has been quantified in animal mod els such as rat and sheep [1][2][3][4][5][6]. In human studies, the maternal-fetal concentration gradients for substrates have been measured at the time of delivery, either by obtaining scalp blood samples or from cord blood samples obtained at the time of elective cesarean section [7][8][9], or cordocen tesis early in gestation [10,11]. The scalp samples or the cord samples obtained at the time of vaginal delivery are confounded by the fact that the process of labor and deliv ery and uterine contractions can cause changes in the ute roplacental blood supply and therefore the gradients mea sured at that time may not reflect the actual maternalfetal relationship during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypoxemiarelated increase in plasma alanine levels in the fetus has been shown in animal and human studies. For example when fetal sheep are exposed to hypobaric hypoxia and human neonates are asphyxiated at birth, the plasma concentration of alanine is increased (41,42). Fetal blood sampling studies have provided evidence of chronic hypoxia and acidosis in the donor twin of chronic TTTS pregnancies (12).…”
mentioning
confidence: 99%